Spinal Anaesthesia Induced Hypotension and Related Adverse Effects in Caesarean Section Delivery and Neonatal Outcome: A Comparison of Using Crystalloid Pre-Loading and Co- Loading in Caesarean Patients - Mohammad, Taneem; Chowdhury, Moinul Hossain; Akter, Shamima; Miah, Mohammad Abdul Karim; Mohammad Mohsin, -; Habib, SM Ahsanul; Sultana, Arifa (International Journal of Human and Health Sciences (IJHHS), 2020)
Background: Volume loading by rapid infusion of crystalloid solution before/during induction of spinal anaesthesia may effectively reduce the incidence of anaesthesia induced hypotension. Objective:To compare the efficacy of crystalloid pre-loading and co-loading to preventhypotension and related adverse effects as well aspoor neonatal outcome in caesarean section delivery under spinal anaesthesia. Methods:This single blinded randomized controlled clinical trial was conducted in the Department of Anaesthesia, Analgesia & Intensive Care, Dhaka Medical College Hospital, Dhaka, between January 2013 and December 2014. A total of 90 patients were selected –45patients of group I received co-loading with Ringer’s lactatesolution, while another 45 patients of group II received a pre-loading of the same fluid.Blood pressure and heart rate were recorded. Ephedrine and adrenaline were administered as needed to treat hypotension.APGAR scores of the newborn were recorded at 1st minute and 5th minute after delivery. Adverse effects like nausea, vomiting, light headedness and shivering was observed all through during operation and post-operative phase in all patients, if any, and recorded. Results:The incidence of hypotension was 17 (37.8%) in group I (co-loading) and 27 (60%) in group II (pre-loading), which was significantly higher in group II (p<0.05).Adverse effects – nausea, vomiting, light headedness and shivering was observed more in group II patients; however, the difference was not statistically significant. In neonates, APGAR score at 1 minute was found ≤7 in 18 (40.0%) from group I, while 28 (62.2%) from group II; the difference was statistically significant (p<0.05). No significant difference was observed in APGAR score at 5 minutes, as found ≤7 in 6 (13.3%) and 3 (6.7%) in group I andgroup II respectively. Conclusion:Severity of hypotension, increased ephedrine requirement and poor APGAR score wereevident in patients who received crystalloid pre-loading group(group II), which meanscrystalloid co-loading group(group I) procedurewas more effective in preventing spinal anaesthesia induced hypotension and secured better neonatal outcome. International Journal of Human and Health Sciences Vol. 05 No. 01 January’21 Page: 90-95